TROP2 targeting reveals therapy-driven cell state dynamics in colorectal cancer - Nuria Vaquero-Siguero; Nikolaos Georgakopoulos; Maria C. Puschhof; Ioannis Chiotakakos; Jasmin Meier; Sigrid K. Fey; Gabriele Diamante; Manuel Mastel; Aitana Guiseris-Martinez; Guillaume Belthier; Nikolai Schleußner; Julia Volk; et al. (Nature, 2026)
Abstract Metastasis remains the leading cause of cancer-related mortality and is driven by pronounced tumour cell plasticity 1 . Here we identify the transmembrane glycoprotein trophoblast cell-surface antigen 2 (TROP2) as a marker of poor-prognosis colorectal cancer (CRC) associated with WNT low , fetal-like tumour cell states that are linked to metastasis and therapy resistance. Functional analyses demonstrate that TROP2 + cells exhibit context-dependent stem-like capacity and the ability to initiate metastatic outgrowth. Given that these detrimental tumour states converge on the cell-surface antigen TROP2, we explored therapeutic targeting of this cell population using clinically relevant TROP2-directed antibody–drug conjugates. Time-resolved analyses reveal therapy-associated dynamics in tumour cell state composition between WNT hi LGR5 + states and WNT low TROP2 + fetal-like states. Conventional chemotherapy promotes the induction of TROP2-expressing cells, whereas TROP2 antibody–drug conjugates selectively target these populations and remodel the tumour cell state landscape. Exploiting this plasticity, combined chemotherapy and TROP2 targeting enhances anti-tumour efficacy in patient-derived models. Together, our findings identify TROP2 as a therapeutic vulnerability of CRC and highlight the importance of targeting tumour cell states to improve therapeutic efficacy and overcome resistance in advanced disease.